Sosialisasi Swamedikasi Penatalaksanaan Demam Pada Ibu PKK - Nutrisia Aquariushinta Sayuti; Nurul Afni; Mutiara Intan Arini; Rizqiana Ayu Safitri; Saputri Fatahna Nurjanah; Tasya Zanuarista; Winda Sari (Poltekkes Kemenkes Surakarta, 2022)
Background: Most people take self-medication to treat fever without a medical examination. It has the potential medication errors caused by unfair practices. To avoid medication errors, knowledge of fever self-medication among PKK members in Hamlet Bentakan RW 13, Danguran Village, South Klaten District, Klaten Regency, needed to be increased. Methods: The research methodology was descriptive. Thirty-four (34) respondents took action. Before the counseling activity, a pretest was administered to respondents—counseling used leaflet media. A post-test was done after the counseling and training. The pretest and post-test were carried out using a question sheet containing 20 questions about self-medication, health workers guiding self-medication, fever, fever medicine and the proper use of fever medicine. Increased knowledge was calculated by the percentage increase in the number of respondents at the level of certain knowledge categories after counseling. Results: The respondents' knowledge level was in the good and sufficient categories. The level of knowledge in the good category before the counseling was 79.4% respondents, while after the counseling was 97.1% respondents. There was an increase in the level of knowledge in the good category of respondents by 17.7%. In contrast, 20.6% of respondents had sufficient knowledge before the counseling. Respondents with a sufficient level of knowledge reduced after the counseling because the knowledge increased towards good by 6 respondents (17.7% of respondents). The respondent's level of knowledge increased following counseling compared to their knowledge before counseling. Age, education, and occupation all affect one's level of knowledge. Conclusion: Respondents suggested being more selective in choosing and using drugs and asking for complete information from pharmacists or pharmaceutical technical personnel. This counseling is suggested to be carried out regularly in various other villages to reduce errors in self-medication practices.